Abstract of the census of the Commonwealth of Massachusetts : taken with reference to facts existing on the first day of June, ... : with remarks on the same ([Printer to the State], 1857)
<1855>- Census of Massachusetts, listed by counties. Included were a table of contents, as well as various tables regarding the sex and race of the population; social statistics, occupation and other relevant information.